Renewing Our Days: Montreal Jews in the Twentieth Century - van Nus, Walter (Labour / Le Travail, 1998)
The article reviews the book, "Renewing Our Days: Montreal Jews in the Twentieth Century," edited by Ira Robinson and Mervin Butofsky.